Nematode Infection Level in Capra hircus on Oesao Rice Fields Area, Kupang Regency, Indonesia - I Gusti Komang Oka Wirawan; Andrijanto Hauferson Angi; Yanse Yane Rumlaklak Rumlaklak; Ni Wayan Apsari Shantika Pratistha; Suryawati Suryawati Suryawati; Stormy Vertygo (Jurnal Sain Veteriner, 2026)
Research objective: to determine the diversity and infection levels of gastrointestinal nematodes in Capra hircus based on age differences in Desa Oesao, Kabupaten Kupang. A total of 30 fecal samples were collected, consisting of 15 samples from young goats and 15 from adult goats, without sex differentiation. Grazing field temperature was also recorded. Samples were examined using sedimentation and flotation methods to identify helminth eggs, while infection intensity was determined using the McMaster method and expressed as eggs per gram (EPG) of feces. The results showed similar nematode diversity in both age groups, except for Chabertia ovina and Ostertagia sp., which were not detected in adult goats. T-test analysis indicated that infection levels in young goats were significantly higher (p < 0.05) than in adults. In young goats, infection levels were highest for Strongyloides papillosus (1,318 EPG) and Haemonchus contortus (700 EPG), followed by Chabertia ovina (67 EPG), Trichostrongylus sp. (63 EPG), Oesophagostomum sp. (43 EPG), Trichuris sp. (43 EPG), and Ostertagia sp. (20 EPG). In adult goats, lower EPG values were recorded for the same species except Chabertia ovina and Ostertagia sp. Infection diversity and intensity were influenced by immunity, age, feed sources, and grazing environment